PELATIHAN PENANGANAN CEDERA DI LAPANGAN BAGI TENAGA KESEHATAN OLAHRAGA JAKARTA - Hidayat Humaid; Tirto Apriyanto; Junaidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract. In order to face high-level competition, high and excellent physical abilities are required. High and excellent physical ability is obtained if the athlete is free from injury. To free athletes from this injury, the role of the health team is very important. The health team here plays a role in maintaining athlete ealth, evaluating athlete health before training sessions, conditioning, health education, injury prevention, medical treatment and rehabilitation. In Indonesia, especially in Jakarta, there are many sports health workers who treat athletes' injuries during training and competitions, but many of them do not have adequate knowledge and skills in handling injuries in the field. Seeing this condition, we were moved to hold sports injury management training in the field for Jakarta sports health workers so that they have the ability to handle athlete injuries well. This training began with problem analysis, training implementation and report preparation from April 2023 to October 2023. Training activities were carried out at the Jakarta High Performance Center - KONI DKI Jakarta and were attended by 30 Jakarta sports health workers. The activity method is carried out through a theoretical approach consisting of material presentation, discussion, and questions and answers and a practical approachconsisting of practices for handling injuries in the field during training and competitions. The output of this activity is an increase in the ability of Jakarta sports health workers to handle injuries on the field during training and competitions. Abstrak. Dalam rangka menghadapi suatu pertandingan tingkat tinggi, diperlukan kemampuan fisik yang tinggi dan prima. Kemampuan fisik yang tinggi dan prima diperoleh apabila atlet terbebas dari cedera. Untuk membebaskan atlet dari cedera ini, peranan tim kesehatan sangatlah penting. Tim kesehatan disini berperan dalam menjaga kesehatan atlet, evaluasi kesehatan atlet sebelum sesi latihan, conditioning, pendidikan kesehatan, pencegahan cedera, pengobatan dan rehabilitasi medik. Di Indonesia, khususnya di Jakarta sudah banyak tenaga kesehatan olahraga yang menangani cedera atlet selama latihan dan kompetisi, namun banyak diantara mereka belum mempunyai pengetahuan dan keterampilan penanganan cedera di lapangan yang memadai. Melihat kondisi ini, kami tergerak untuk mengadakan pelatihan penanganan cedera olahraga di lapangan bagi tenaga kesehatan olahraga Jakarta agar mempunyai kemampuan menangani cedera atlet dengan baik. Pelatihan ini dimulai dengan analisa masalah, pelaksanaan pelatihan dan pembuatan laporan pada bulan april 2023 sampai bulan oktober 2023. Kegiatan pelatihan dilaksanakan di Jakarta High Performance Center - KONI DKI Jakarta, dan diikuti 30 tenaga kesehatan olahraga Jakarta. Metode kegiatan dilakukan melalui pendekatan teoritis yang terdiri dari pemaparan materi, diskusi, dan tanya jawab dan pendekatan praktek yang terdiri dari prektek penanganan cedera di lapangan selama latihan dan kompetisi. Luaran dari kegiatan ini berupa peningkatan kemampuan tenaga kesehatan olahraga Jakarta menangani cedera di lapangan selama latihan dan kompetisi.